A case of ostium secundum atrial septal defect for major decompressive spine surgery – covering the paths still left untreaded - Nidhi Sultania; Priyanka Bansal; Kunal Bansal (Asian Journal of Medical Sciences, 2024)
Atrial septal defect (ASD) accounts for 35% of all congenital heart diseases in adults. Patients usually present in their twenties or thirties owing to gradually progressive right ventricular remodeling because of left to right shunt, right-sided heart failure, and pulmonary hypertension. In this case report, we present the management of young female patient with ASD posted for D5 spine decompression and fixation. Patients with congenital heart disease for spine surgery present with unique set of challenges for anesthesiologists. Well-prepared anesthesia plan is essential to prevent increase in shunt fraction, shunt reversal, hypoxia, hypercapnia, acidosis, and hypothermia along with careful addressal of positioning issues to ensure smooth recovery of patient.